Novel fractal antenna for UWB applications using the coplanar waveguide feed line - Akram El Hamdouni; Abdelali Tajmouati; Jamal Zbito; Abdelwahed Tribak; Mohamed Latrach (Institute of Advanced Engineering and Science, 2019)
In this study an original Coplanar Waveguide (CPW) antenna has been achieved into simulation and manufacturing in order to be an important candidate for the Ultra-wideband applications. The area of the proposed structure is 34mm x 43mm operating in the frequency range 3.1 GHz – 10.6 GHz released as UWB by the Federal Communications Commission (FCC). To perform the design of the proposed CPW antenna two electromagnetic solvers has been adopted which are CST of Microwave Studio and ADS of Agilent. The radiating patch has been chosen circular with fractal geometry based on circular slots with different sizes. The dielectric substrate is an Epoxy FR4 with a Relative permittivity 4.4, a thickness 1.6 and a loss tangent 0.025. To valid the functionality of the antenna two parameters has been computed which are the coefficient of reflection and the radiation pattern and confirmed into measurement by using the Network Analyser and the anechoic chamber.